2007
DOI: 10.1002/hep.21498
|View full text |Cite
|
Sign up to set email alerts
|

IL-10, regulatory T cells, and Kupffer cells mediate tolerance in concanavalin A–induced liver injury in mice

Abstract: The liver appears to play an important role in immunological tolerance, for example, during allo-transplantation. We investigated tolerance mechanisms in the model of concanavalin A (ConA)-induced immune-mediated liver injury in mice. We found that a single injection of a sublethal ConA dose to C57BL/6 mice induced tolerance toward ConA-induced liver damage within 8 days. This

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
246
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 240 publications
(267 citation statements)
references
References 50 publications
19
246
2
Order By: Relevance
“…Betulin reduces serum levels of IFN-γ, TNF-α, and IL-6 in mice with hepatitis Several lines of evidence suggest that IFN-γ [16,17] , TNF-α [18,19] , IL-4 [20] , and IL-17 [21,22] promote hepatic damage, whereas IL-10 [23] protects the liver from injury, and IL-6 [18] has varying effects depending on the stage of Con A-induced hepatitis at which it is present. To ascertain whether betulin interfered with the systemic levels of these cytokines, we examined the serum levels of IFN-γ, TNF-α, IL-2, IL-4, IL-6, IL-10, and IL-17 by using a CBA kit.…”
Section: Resultsmentioning
confidence: 99%
“…Betulin reduces serum levels of IFN-γ, TNF-α, and IL-6 in mice with hepatitis Several lines of evidence suggest that IFN-γ [16,17] , TNF-α [18,19] , IL-4 [20] , and IL-17 [21,22] promote hepatic damage, whereas IL-10 [23] protects the liver from injury, and IL-6 [18] has varying effects depending on the stage of Con A-induced hepatitis at which it is present. To ascertain whether betulin interfered with the systemic levels of these cytokines, we examined the serum levels of IFN-γ, TNF-α, IL-2, IL-4, IL-6, IL-10, and IL-17 by using a CBA kit.…”
Section: Resultsmentioning
confidence: 99%
“…Given that the A allele at position -571 always segregates with the A allele at position -1061, it is possible that an interaction can occur between the transcription factors that bind to these sites. Studies of Con A treated T cells suggested that stimulation leads to production of T cells with a regulatory phenotype [38]. We tested whether or not there were differences in IL-10 production from thymic derived natural T regulatory cells that correlated with IL-10 genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Immune pathology in this model shares certain features with autoimmune hepatitis, specifically: relevance of CD4 + T cells, genetic prevalence of certain mouse strains in terms of susceptibility, gender-related differences, and immunosuppression during remission. We have recently described that IL-10-producing CD4 + CD25 + Foxp3 + Tregs, but not immuneregulatory NKT cells, mediate long-lasting tolerance against Con A restimulation that develops 8 d after the first Con A injection and is characterized by suppression of the Th1/Th17 responses and liver damage (12). Moreover, Tregs from tolerant mice have a higher immunosuppressive activity in vivo and in vitro compared with those from nonpretreated animals.…”
Section: Hemokines Mediate Migration Of Immune Cells Into In-mentioning
confidence: 99%
“…Primer pairs were used as described previously (4,12). Relative mRNA levels were calculated after normalization to b-actin or GAPDH, using the CFX96 Manager software.…”
Section: Expression Analysis Of Chemokines/cytokinesmentioning
confidence: 99%
See 1 more Smart Citation